2021
DOI: 10.3346/jkms.2021.36.e178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Clipping and Coiling in Elderly Patients with Unruptured Cerebral Aneurysms: a National Cohort Study in Korea

Abstract: Background We aimed to analyze outcomes of clipping and coiling in treating unruptured intracranial aneurysms (UIAs) in elderly patients and to identify the age at which perioperative risk increases based on national cohort data in South Korea. Methods The incidence of perioperative intracranial hemorrhage (ICRH), perioperative cerebral infarction (CI), mortality, and moderate to severe disability data of the patients who underwent coiling or clipping for UIAs were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As a result, the morbidity and mortality rates were 0.38% and 1.16%, respectively. Although this was an improvement in the clinical outcomes of CE for UIAs from 2006 to 2008 in Korea, the incidence of procedure-related CI in Korea was higher than that reported in previous literature [ 14 ]. As the results of this study show, from 2013 to 2018, the number of hospitals equipped for CE procedures increased by 1.69 times, of which GHs increased by 1.53 times and sGHs increased by 2.18 times.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As a result, the morbidity and mortality rates were 0.38% and 1.16%, respectively. Although this was an improvement in the clinical outcomes of CE for UIAs from 2006 to 2008 in Korea, the incidence of procedure-related CI in Korea was higher than that reported in previous literature [ 14 ]. As the results of this study show, from 2013 to 2018, the number of hospitals equipped for CE procedures increased by 1.69 times, of which GHs increased by 1.53 times and sGHs increased by 2.18 times.…”
Section: Discussionmentioning
confidence: 82%
“…In 2021, a study analyzing treatment outcomes in the entire Korean population with UIAs was published [ 14 ], and it was reported that the rate of complications was higher than that reported in other existing studies. It was hypothesized the quality of treatment decreased because of the rapid increase in the number of hospitals equipped for CE in recent years, and it was also hypothesized that the variation in treatment experience by region and hospital size also affected treatment quality [ 5 , 7 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the discovered connectivity between chronic obstructive pulmonary diseases and UIA in women older than 60 years can direct a diagnostic workout toward identifying hidden subclinical forms of COPD in non-smoking aneurysm carries in the respective age. The previous paradigm of age limitation (not older than 65 years) in selection cases for an active treatment of UIA currently is shifting toward higher age limits and is more dependent on the patient’s co-morbidities, functional status, and local life-expectancy rates 21 . The sets of co-morbidities discovered in our age and gender stratified networks may help in the prediction of health status and phenotypical changes in UIA patients even in the long run, thus helping to optimize a timing of active treatment.…”
Section: Discussionmentioning
confidence: 99%
“…IAs in the elderly population are not very well documented due to a lack of large-sample studies. In addition, existing studies have mainly focused on patients with unruptured aneurysms [6][7][8][9]. Subsequently, the overall characteristics of IAs in elderly patients remain unclear.…”
Section: Discussionmentioning
confidence: 99%